PENGARUH PERPUTARAN KAS DAN PERPUTARAN PIUTANG TERHADAP RETURN ON ASSET (ROA) - Ela Widasari; Seli Apriyanti (The Asia Pacific Journal Of Management Studies, 2017)
This study aims to determine the effect of Cash Turnover and Receivable Turnover to Return On Asset in lq45 Companies Listed In Indonesia Stock Exchange Period 2011-2016. Return On Asset is a ratio that reflects how much return the company receives in the form of profit on investments that have been invested in the company. The higher the return on assets the better the state of the company.The method used in this research is a quantitive method. The sampling technique used is Purposive Sampling, from the criteria that have been specified the sampel used as many as 7 companies and using secondary data from the Indonesia Stock Exchange is Manufacturing Companies lq45 Period 2011-2016. The statistical test used is descriptive statistics test, classical assumption, multiple linear regression analysis, correlation analysis, hypothesis test, adan coefficient determination using SPSS V20 application program.From the partial test shows that the Cash Turnover has a significant negative effect to Return On Asset with a significant level 0.000 < 0.05. while the Receivable Turnover has a significant negative effect to Return On Asset with a significant level of 0.002 < 0.05. Simultaneously Cash Turnover and Receivable Turnover have a significant influence to Return On Asset with significant level 0.000 < 0.05 and coefficient of determination equal to 84%.Based on the result of data analysis, it can be concluded that Cash Turnover and Receivable Turnover have significant effect to Return On Asset in lq45 Companies Listed In Indonesia Stock Exchange Period 2011-2016. It is expected for the next research to be able to add the variables related to working capital and expand the different sample research in order to get better results.